Tissue injury and remodeling in rat hippocampal dentate gyrus following sodium-potassium-ATPase inhibition. - Omar, Ayman I. (University of Ottawa (Canada), 2002)
Na+, K+-ATPase is a ubiquitous membrane enzyme that plays an important role in maintaining neuronal excitability, ionic homeostasis and cell survival. Although failure of the Na+, K+-ATPase pump has been implicated in the pathophysiology of a variety of neurological conditions, the timeline and precise sequence of events at the cellular and subcellular levels that follow failure of the pump remain elusive, particularly in the in vivo environment. To this end, we developed an animal model and a set of fluorescence-based cell tagging methods during this thesis research. The methodology involves stereotactically coinfusing the Na+, K+-ATPase pump blocker, ouabain with a set of fluorescent tags into the hippocampal dentate gyrus. These fluorescent tags, by undergoing fluorescence enhancement upon binding to specific subcellular targets, therefore allow the probing of subcellular dynamics in vivo following inhibition of the Na+, K+-pump. Based on this original methodology, we describe several novel types of tissue injury in the rat dentate gyrus following pump failure, which can be summarized as follows: (1) Pump inhibition results in an increase in membrane porosity that occurs as early as the 1-hour time point. Furthermore, pump inhibition enhances uptake of the lipophilic probe, DiI into plasma membranes of dentate granule cells. This increase in DiI incorporation is associated with the appearance of reactive changes characterizing early neuronal injury. Our results suggest that pump inhibition leads to an early increase in membrane permeability followed by a change in membrane phospholipid structure. (2) Pump inhibition triggers a form of cell death with "mixed" apoptotic and necrotic features. The broad-spectrum K+ channel blocker, charybdotoxin is capable of significantly attenuating the neuronal damage associated with inhibition of the Na+, K+ pump, indicating that loss of intracellular K+ plays an important role in cell death associated with pump inhibition. (3) We describe a novel tissue response whereby pump inhibition triggers the appearance of a radial glia-like cell population that undergoes time-dependent cell dispersion and rearrangement. (4) We found that pump inhibition can simultaneously trigger cell death as well as upregulate progenitor cell proliferation. Migration of such newly born progenitor cells was also enhanced towards areas of cell injury and tissue damage. We suggest that such a host of tissue responses may represent an early endogenous attempt at restoring tissue structural integrity, through the enhancement of proliferation and migration of neural precursor cells as well as re-expression of the radial glial scaffold necessary for progenitor cell migration. The experimental data reported in this thesis may therefore have important implications in the future development of therapeutic strategies aimed at restoring tissue structural integrity and possibly functional outcome following central nervous system injury.
Keywords: Biology, Neuroscience.